Reversible and easy post-crosslinking method for developing a surface ion-imprinted hypercrosslinked monolith for specific Cd(ii) ion removal from aqueous solutions. Issue 91 (16th September 2016) - Çorman, Mehmet Emin; Armutcu, Canan; Uzun, Lokman; Say, Rıdvan; Denizli, Adil
Abstract : In this study, a new surface imprinting technique for preparing a hypercrosslinked monolith to selectively remove Cd(ii ) ions out from aqueous solutions was proposed. Abstract : In this study, a new surface imprinting technique for preparing a hypercrosslinked monolith to remove Cd(ii ) ions out from aqueous solutions was proposed. The monoliths were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, thermal gravimetrical analysis, surface area measurements and elemental analysis. The reversible nature of the hypercrosslinking process was proved by repeated crosslinking and denaturation cycles by using ferric ions as an oxidant and urea as a reductant, respectively meanwhile performing surface area measurements for both situations to demonstrate the variation in the surface porosity. The multipoint BET surface areas of poly(HEMA), surface ion imprinted (Cd–SII-HM) and non-imprinted (NI-HM) monoliths were determined as 269.1 m 2 g −1, 79.1 m 2 g −1, and 67.4 m 2 g −1, respectively. By breaking hypercrosslinks, the micropore volume decreased from 39.7 mm 3 g −1 to 11.8 mm 3 g −1 while the cumulative pore volume decreased from 30.7 mm 3 g −1 to 9.1 mm 3 g −1 during urea treatment. At the first step, the affecting factors such as initial Cd(ii ) ion concentrations, pH and adsorption time were optimized. Then, the selectivity of the Cd–SII-HM for Cd(ii ) against other metal ions was evaluated not only from singular solutions but also from triple and quadruple solutions, which included Pb(ii ), Zn(ii ) and Hg(ii ) ions as competitors. The relative selectivity coefficients were calculated as 3.28, 15.61 and 58.55 for Cd(ii )/Zn(ii ), Cd(ii )/Pb(ii ) and Cd(ii )/Hg(ii ) pairs. The results obtained indicated that the developed reversible and easy post-crosslinking method is quite applicable for producing the surface ion-imprinted polymers with high selectivity for the template ions [Cd(ii )] regarding the potential competitor ions [Zn(ii ), Pb(ii ) and Hg(ii )].